Length-Weight Relationships and Morphological Variability of BlackStriped Pipefish Syngnathus abaster Risso, 1827 in the Dnieper River Basin - Khrystenko, Dmytro; Христенко, Дмитро Сергійович; Kotovska, Ganna; Котовська, Ганна Олександрівна; Novitsky, R. A.; Novitsky, R. O.; Novitskiy, R. A.; Novitskiy, R. O.; Novickii, R. A.; Novitskij, R. A.; Novitskij, R. O.; Nowicki, R. A.; et al. (Central Fisheries Research Institute. Trabzon, TURKEY, 2015)
Length-weight relationships and morphological variability were assessed for black-striped pipefish Sygnathusabaster Risso, 1827 that has successfully spread in freshwater ecosystems of Ponto-Caspian basin. Ninety females and ninety males were analyzed. Their standard length was 10.65±0.9 cm, ranged 6.90–14.10 cm and the wet weight – 0.71±0.02 g (0.15 – 1.53 g) respectively. The length-weight relationships were significant (P≤ 0.05) for all samples. The R2 values ranged from 0.869 to 0.949. In terms of growth, males in all observed areas were positively allometric (b > 3), while females showed isometry (b = 3).Poled samples (males + females) were positively allometric. In addition, measurements of thirteen morphometric characters allowed indicating several morphological differences of individuals from several samples. They manifested in body and head proportions, fins position and body heights with P≤0.05. Furthermore, principal components analysis allowed us to differentiatefish from lacustrine and stream habitats into two separate scatters by external morphology that proved the availability of some different ckreods (ontogenetic channels) of black-striped pipefish. One of them was implemented in lotic ecosystems of the lacustrine parts and another in lentic stream parts of Dnieper reservoirs. Оцінювали розмірно-вагові характеристики та морфологічну мінливість чорноморської пухлощокої голки-риби Syngnathus abaster Risso, 1827 р., яка успішно поширена у прісноводних екосистемах Понто-Каспійського басейну. Проаналізовано 90 самок і 90 самців. Стандартна їх довжина становила 10,65 ± 0,9 см, коливалася від 6,90 до 14,10 см, а вологої ваги - 0,71 ± 0,02 г (0,15–1,53 г) відповідно. Співвідношення довжини та ваги було значним (P≤0,05) для всіх зразків. Значення R2 коливались від 0,899 до 0,949. З точки зору зростання, самці у всіх спостережуваних областях були позитивно аллометричними (b> 3), тоді як самки показали ізометрію (b = 3). Відібрані зразки (самці + самки) були позитивно аллометричними. Крім того, вимірювання тринадцяти морфометричних ознак дозволило вказувати на кілька морфологічних відмінностей осіб від декількох зразків. Вони проявляються у пропорціях тіла та голови, положеннях плавців та висоті тіла з високою достовірністю (P≤0,05). Крім того, аналіз основних компонентів дозволив нам ідентифікувати різні умови існування морськї голки-риби за морфологічними ознаками. Доведена наявність деяких різних онтогенетичних каналів Syngnathus abaster. Один з них притаманний для лотичних екосистем (озерних ділянок), а інший – для лентичних екосистем (річкових ділянок) дніпровських водосховищ.
Розмірно-вагові показники та морфологічна мінливість чорноморської пухлощокої голки-риби Syngnathus abaster Risso, 1827 у басейні р. Дніпро
Keywords: black-striped pipefish; чорноморська пухлощока голка-риба; syngnathidae; Голкові; length-weight relationships; розмірно-вагові показники; morphological variability; морфологічна мінливість; ontogenetic channels; онтогенетичні канали розвитку